Process optimization for the anaerobic digestion of poplar (Populus L.) leaves. Issue 1 (1st January 2020) - Zhang, Shuqing; Wang, Yanling; Liu, Shengyong
ABSTRACT: This study investigates the optimized condition for enhancing biogas production in the anaerobic digestion of fallen poplar leaves. Two experiments were conducted: (1) The calcium hydroxide concentration, bacteria concentration, and composting time were used as three parameters to optimize the fermentation pretreatment condition and contrasting tests were performed; and (2) a series of fermentation tests were conducted to explore the best process parameters and biogas production characteristics. The results showed that a biological and chemical combined pretreatment effectively improved the biogas productivity of poplar leaves as fermentation substrates, and the parameter that had the greatest effect during anaerobic digestion was temperature followed by the solid concentration and pH value. The optimal pretreatment condition was: alkali concentration 4.61%, bacterial concentration 0.20‰, and a composting time of 6.6 days. By considering the factors that affect the fermentation of poplar leaves and the cumulative gas production, the optimum condition for poplar leave digestion was found to be a temperature of 30°C, a pH of 7, and a 10% solid concentration. In addition, the methane yield of the optimized trial was well fitted using the modified Gompertz model. Graphical abstract: